A New Reading of Kant's Theory of Punishment - Hoffman, Robert (2015)
There are deep, insurmountable difficulties with the traditional interpretation of Immanuel Kantâ??s writings on the subject of punishment. Although it is undeniable that throughout his published writings on practical philosophy â?? and in particular in his Metaphysics of Morals â?? he consistently advocates for the view that punishment can only be justified as a direct response to an individualâ??s act of wrongdoing, his status as one of the foremost theorists in the retributivist pantheon is philosophically untenable. In this dissertation, I articulate the ways in which Kantâ??s explicit support for retributivism directly contradicts more foundational elements of his practical philosophy and argue instead that he has the resources to consistently construct a deterrent theory of punishment. In particular, I highlight Kantâ??s division of duties and his conception of the state to demonstrate that the idea of a political community retributively responding to moral desert is wholly incompatible with Kantian principles. In order to overcome these obstacles, I develop a new approach to Kantian deterrence â?? which I call Kantian Protective Deterrence â?? that grounds the stateâ??s right to exercise coercive force against its citizens in what Kant understood to be its fundamental role of protecting each individual citizen from violations of her or his right to exercise external freedoms